Composite cement materials based on β-tricalcium phosphate, calcium sulfate, and a mixture of polyvinyl alcohol and polyvinylpyrrolidone intended for osteanagenesis - Stepanova, Ksenia; Lytkina, Darya N.; Sadykov, Rustam; Shalygina, Kseniya; Khojazoda, Toir; Mahmadbegov, Rashidjon; Kurzina, Irina A. (Polymers)
The primary purpose of the study, presented in this article, was to obtain a composite cement material intended for osteanagenesis. The -tricalcium phosphate powder (beta-TCP, beta-Ca3(PO4)2) was obtained by the liquid-phase method. Setting and hardening of the cement system were achieved by adding calcium sulfate hemihydrate (CSH, CaSO41/2H2O). An aqueous solution of polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and a PVA/PVP mixture were used as a polymer component. The methods of capillary viscometry and Fourier-transform infrared spectroscopy (FTIR) revealed the formation of intermolecular hydrogen bonds between polymer components, which determines the good miscibility of polymers. The physicochemical properties of the synthesized materials were characterized by X-ray diffraction (XRD) and FTIR methods, and the added amount of polymers does not significantly influence the processes of phase formation and crystallization of the system. The size of crystallites CSD remained in the range of 32–36 nm, regardless of the ratio of polymer components. The influence of the composition of composites on their solubility was investigated. In view of the lower solubility of pure beta-TCP, as compared to calcium sulfate dihydrate (CSD, CaSO42H2O), the solubility of composite materials is determined to a greater degree by the CSD solubility. Complexometric titration showed that the interaction between PVA and PVP impeded the diffusion of calcium ions, and at a ratio of PVA to PVP of 1/1, the smallest exit of calcium ions from the system is observed. The cytotoxicity analysis results allowed us to establish the fact that the viability of human macrophages in the presence of the samples varied from 80 % to 125 % as compared to the control.